REPRESENTATION OF THE CONCEPTS OF "HUMAN AND NATURE" IN THE WORKS OF DORIS LESSING - Alizhonova Okila Alimovna (Research Focus International Scientific Journal, 2025)
This article examines the interpretation of the concepts of "nature and man" in the works of English writer Doris Lessing. Lessing, in his works, deeply analyzes the complex relationship between man and nature, showing the interdependence between these two concepts. In his works, nature appears not only as a background, but as an integral part of human life. Lessing sees nature as an important factor in the formation of the human psyche and psychology, which leads to the study of the interaction between the inner world of man and the external environment in his works.